Role Of Raphe In The Body Temperature Regulation Of Precocious Birds - Caroline Cristina Silva; Welex Cândido Silva; Luciane Helena Gargaglioni; Kênia Cardoso Bícego (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: It is demonstrated in mammals that, at least in rats, caudal brain regions, such as raphe nuclei, are involved in the modulation of thermoeffectors for heat loss and heat production, such as peripheral vasodilation/vasoconstriction, nonshivering and shivering thermogenesis. If the same scenario occurs in the other group of endothermic vertebrates, i.e., birds, it is still completely unknown.